Formation method of electrode foil for electrolytic capacitor of photovoltaic inverter

Anodizing the multi-stage composite liquid through anodizing, the problems of hole blockage of electrode foil and insufficient density of oxide film were solved, and high-performance electrode foil suitable for photovoltaic inverter capacitors were prepared.

CN119480459APending Publication Date: 2025-02-18GUANGXI HEZHOU GUIDONG ELECTRONICS TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411325353.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, when preparing electrode foil for high-voltage aluminum electrolytic capacitors, partial hole blockage is prone to occur, resulting in capacity loss, insufficient oxide film, large loss, and high voltage, high ripple resistance and long life of the prepared electrode foil. The characteristics of the same are relatively poor and are not suitable for photovoltaic inverter capacitors.

Method used

Large-pore corrosion foil is used and anodized multiple times through multi-stage composite liquid, including boiling treatment, multi-stage transformation and multiple repairs to form a high-density oxide film, improving the voltage and ripple resistance of the electrode foil .

Benefits of technology

The prepared electrode foil has the characteristics of high voltage, high ripple resistance, long life, etc., which can meet the requirements of photovoltaic inverter aluminum electrolytic capacitors and improve the reliability of the capacitor.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a formation method of an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter, which comprises the following steps of: preparing a composite formation liquid from two or more substances such as ammonium adipate, ammonium formate, hypophosphite, citric acid, maleic acid or fumaric acid in the preceding-stage formation, and preparing a composite formation liquid from boric acid, azelaic acid and salts thereof in the final-stage formation, the composite formation liquid has very high oxidation efficiency, and has the characteristics of inhibiting the reaction between the surface of aluminum oxide and water, dissolving a feather-shaped layer of a hydration film on the surface of aluminum foil, enhancing the compactness of the oxidation film, improving the voltage resistance of the oxidation film in unit thickness, reducing leakage current, improving the hydration resistance and the like. And the anode foil oxide film prepared by performing multi-stage depolarization after formation has the characteristics of high voltage, high ripple resistance, long service life and the like, and can meet the requirements of an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode foil formation, and in particular relates to a method for forming an electrode foil for an electrolytic capacitor of a photovoltaic inverter. Background Art

[0002] Photovoltaic solar power generation technology has the advantages of being environmentally friendly, pollution-free, and energy-saving. In addition, solar energy is widely distributed on the earth and has no consumption restrictions. The photovoltaic solar power generation industry will become one of the rapidly developing new energy industries. Since the current generated by the photovoltaic solar power generation system is direct current, but the transmission power and civil power are mainly powered by alternating current, this means that solar power generation must convert direct current into alternating current through an inverter. The main function of the inverter is to convert the variable DC voltage input of the power supply into an interference-free AC sine wave output, which can be used by the equipment and can also be fed back to the power grid. At the same time, it also has the function of maximizing the performance of solar cells and the system fault protection function. The inverter is a key component in the solar photovoltaic power generation system and is the brain of the photovoltaic power generation system. The inverter is used in a harsh environment with large temperature differences. One of the keys to improving the reliability of photovoltaic inverters is to improve the reliability of electrolytic capacitors.

[0003] Photovoltaic inverter electrolytic capacitor requirements: high voltage (generally high-power photovoltaic inverters directly integrate the converted AC power into the high-voltage power grid, but from the perspective of safety regulations, the output voltage of photovoltaic battery groups is generally not higher than 900V, and two 450V electrolytic capacitors can be selected in series, but in order to improve safety, two 500V electrolytic capacitors can be selected in series, or higher voltage electrolytic capacitors), high ripple resistance (generally the current flowing through the capacitor of a photovoltaic inverter is 0.44 times the effective value of the inverter output current), and long life (generally 5 to 10 years). The electrode foil is the heart of the capacitor, so the electrode foil is required to have the following characteristics: high voltage, high ripple resistance, long life, etc.; the requirements are completely different from those of conventional anode foil.

[0004] The voltage of anode foil used in conventional high-voltage aluminum electrolytic capacitors is usually lower than 700V, and the etched holes of the used corrosion foil are generally below 1.1μm. When it is formed in a conventional forming solution at a voltage above 700V, it is prone to partial pore blockage, capacity loss, insufficient density of the oxide film, and large losses. The prepared electrode foil has relatively poor properties such as high voltage, high ripple resistance, and long life, and is not suitable for the production of photovoltaic inverter capacitors. Summary of the invention

[0005] Aiming at the problem that when the corrosion foil is subjected to chemical formation at a voltage of more than 700V using a conventional chemical forming liquid, partial pore blockage is likely to occur, resulting in capacity loss, insufficient density of the oxide film, relatively large loss, and relatively poor characteristics of the prepared electrode foil such as high voltage, high ripple resistance, and long life, the present invention provides a chemical forming method for electrode foil for photovoltaic inverter aluminum electrolytic capacitors, and prepares electrode foil with the characteristics of high voltage, high ripple resistance, and long life for making photovoltaic inverter aluminum electrolytic capacitors.

[0006] The present invention is achieved through the following technical solutions: A method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter comprises the following steps: S1: Take a large-aperture etched foil and boil it in pure water for 12 to 16 minutes; place the boiled etched foil in a composite chemical solution a for first-stage chemical formation, with a chemical voltage of 15% of the applied voltage and a chemical time of 8 to 12 minutes to obtain a first-stage chemically formed aluminum foil; The composite chemical liquid a is a mixed solution containing 1-4wt% boric acid, 0.4-1.0wt% citric acid, 0.2-0.5wt% ammonium adipate, 0.01-0.05wt% ammonium formate or ammonium phthalate or ammonium benzoate, and 0.01-0.05wt% ammonium hypophosphite; S2: placing the primary chemically formed aluminum foil in the composite chemically formed liquid b for the second stage chemically formed, the chemically formed voltage is 30% of the applied voltage, the chemically formed time is 8 to 12 minutes, and the secondary chemically formed aluminum foil is obtained; The composite chemical forming liquid b is a mixed solution containing 1-4wt% boric acid, 0.4-0.8wt% citric acid, 0.2-0.4wt% ammonium adipate, 0.01-0.05wt% ammonium formate or ammonium phthalate or ammonium benzoate, and 0.01-0.05wt% ammonium hypophosphite; S3: placing the secondary chemically formed aluminum foil in the composite chemically formed liquid c for the third chemically formed, the chemically formed voltage is 45% of the applied voltage, the chemically formed time is 8 to 12 minutes, and the tertiary chemically formed aluminum foil is obtained; The composite chemical liquid c is a mixed solution containing 1-4wt% boric acid, 0.2-0.4wt% citric acid, 0.1-0.2wt% ammonium adipate, and 0.005-0.01wt% maleic acid or fumaric acid; S4: placing the three-stage chemically formed aluminum foil in the composite chemical liquid d for the fourth stage chemically forming, the chemically forming voltage is 60% of the applied voltage, the chemically forming time is 8 to 12 minutes, and the four-stage chemically formed aluminum foil is obtained; The composite chemical liquid d is a mixed solution containing 1-4wt% boric acid, 0.1-0.2wt% citric acid, and 0.05-0.1wt% ammonium adipate; S5: placing the four-stage chemically formed aluminum foil in the composite chemical forming liquid e for the fifth stage chemical forming, the chemical forming voltage is 75% of the applied voltage, the chemical forming time is 8 to 12 minutes, and the five-stage chemically formed aluminum foil is obtained; The composite chemical solution e is a mixed solution containing 4-8wt% boric acid, 0.005-0.01wt% azelaic acid, and 0.005-0.1wt% ammonium pentaborate; S6: placing the five-level chemically formed aluminum foil in the composite chemically formed liquid f for the sixth level chemically formed, the chemically formed voltage is 90% of the voltage to be applied, the chemically formed time is 10 to 16 minutes, and the six-level chemically formed aluminum foil is obtained; The composite chemical liquid f is a mixed solution containing 4-8wt% boric acid, 0.002-0.01wt% azelaic acid, and 0.005-0.04wt% ammonium pentaborate; S7: placing the six-stage chemically formed aluminum foil in the composite chemical forming liquid g for the seventh stage chemical forming, the chemical forming voltage is 100% of the voltage to be applied, the chemical forming time is 30 to 40 minutes, and the seven-stage chemically formed aluminum foil is obtained; The composite chemical liquid g is a mixed solution containing 4-6wt% boric acid, 0.001-0.01wt% azelaic acid, and 0.005-0.015wt% ammonium pentaborate; S8: performing a first heat treatment on the seven-level chemically formed aluminum foil, the treatment temperature is 450-550° C., and the treatment time is 1-3 min; S9: performing a first repair chemical treatment on the heat-treated aluminum foil, the repair chemical treatment time being 10 to 15 minutes; then placing the aluminum foil after the first repair chemical treatment in a 5 to 8 wt % phosphoric acid solution, and treating at 55 to 70° C. for 10 to 15 minutes; S10: performing a second repair and chemical treatment on the aluminum foil after the phosphoric acid treatment in step S9, and the repair and chemical treatment time is 10 to 15 minutes; S11: subjecting the aluminum foil after the second repair to a second heat treatment, the treatment temperature is 450-550° C., and the treatment time is 1-3 min; S12: The aluminum foil after the second heat treatment is repaired and formed three times, and the repairing and forming time is 10 to 15 minutes; S13: placing the aluminum foil after the third repair in a 0.05-0.1 wt % phosphoric acid solution and treating it at room temperature for 1-5 min; S14: drying the aluminum foil treated with phosphoric acid in step S13 at 200-300° C. for 2-4 minutes to obtain an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter.

[0007] Preferably, the diameter of the corrosion holes of the large-aperture corrosion foil is ≥1.4 μm.

[0008] Preferably, the applied voltage is 760V to 850V.

[0009] Preferably, the repair formation is carried out in a composite formation liquid g.

[0010] Preferably, the repair formation voltage is 100% of the voltage to be applied.

[0011] The present invention uses an etching foil with an etched hole diameter of more than 1.4 μm, which ensures that an oxide film is formed in the etched hole after being formed at more than 700 Vf, and the wall layer is thickened, avoiding the phenomenon of etched holes being blocked, so that the etched foil has an electrical path, fully exerts the effective electrode function, and does not lose capacity. At the same time, the etched hole diameter is ≥1.4 μm, which can reduce the influence of being used for liquid resistance heating and shortening the life. After the etched foil is boiled, it is anodized in a composite forming liquid composed of two or more of boric acid, citric acid, adipic acid, azelaic acid, formic acid or phthalic acid or benzoic acid, hypophosphorous acid, maleic acid or fumaric acid and their ammonium salts, wherein: Adipic acidization can make the oxide film generated by the corroded foil denser, with higher specific volume and bending conversion rate.

[0012] Boric acid solution can make the oxide film generated by corroding foil have good dielectric properties, but its hydration resistance is weak.

[0013] Phosphate forming liquid can make the corroded foil form AlPO4 or P2O5 to replace the aluminum atoms in the lattice, forming a strong network structure connected by oxygen bonds, which obviously inhibits hydration and solves the drawbacks of borate forming liquid, making the produced oxide film very stable.

[0014] Azelaic acid-based forming liquid has high oxidation efficiency, and the generated oxide film is relatively fine and thin, with relatively high specific volume and bending conversion rates. However, azelaic acid has low solubility and low conductivity, making it suitable for medium and high voltage formation. Therefore, it is used in the final formation (four to seven levels) step.

[0015] Adding citric acid to the chemical forming solution can improve the solubility of the porous hydroxide on the outer layer of the chemical forming film, which is beneficial to the formation of a crystallized chemical forming film, can reduce the thickness of the oxide film, increase the gain rate of the actual area of ​​the oxide film, and improve the specific capacitance.

[0016] Adding maleic acid or fumaric acid, hypophosphorous acid and its ammonium salt can promote uniform formation, promote film formation and repair oxide film, reduce surface defects, increase density, improve wide temperature characteristics, hydration resistance, reduce leakage current and other properties.

[0017] Ammonium formate, ammonium phthalate or ammonium benzoate is easily ionized and can form a modified layer on the surface of the electrode foil, which helps to improve the interface properties between the electrode and the electrolyte, reduce the interface impedance, effectively improve the conductivity of the electrolyte, improve the formation efficiency, and improve the film stability and service life.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: The present invention uses two or more substances such as ammonium adipate, ammonium formate, hypophosphite, citric acid, maleic acid or fumaric acid to prepare composite chemical liquid in the pre-stage chemical formation (stage one to three), and uses boric acid, azelaic acid and its salts to prepare composite chemical liquid in the final stage chemical formation (stage four to seven). These composite chemical liquids have high oxidation efficiency, can inhibit the reaction between aluminum oxide surface and water, dissolve the feather-like layer of hydrated film on the surface of aluminum foil, enhance the density of oxide film, improve the voltage resistance per unit thickness of oxide film, reduce leakage current, improve hydration resistance, etc. After chemical formation, it is subjected to multi-stage depolarization, and the obtained anode foil oxide film has the characteristics of high voltage, high ripple resistance, long life, etc., and can meet the requirements of electrode foil for aluminum electrolytic capacitors of photovoltaic inverters. DETAILED DESCRIPTION

[0019] The present invention is further described below with reference to the embodiments. In the embodiments, unless otherwise specified, the technical means used are all conventional technical means in the art. Example

[0020] A method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter comprises the following steps: S1: Take a corrosion foil with a corrosion hole diameter of ≥1.4μm, boil it in pure water for 12min; place the boiled corrosion foil in a composite chemical solution a for the first stage chemical formation, the chemical formation voltage is 115V, the chemical formation time is 8-12min, and a first-stage chemically formed aluminum foil is obtained; The composite chemical liquid a is a mixed solution containing 1wt% boric acid, 1.0wt% citric acid, 0.5wt% ammonium adipate, 0.05wt% ammonium formate, and 0.05wt% ammonium hypophosphite; S2: placing the primary formed aluminum foil in the composite forming solution b for second-stage forming, the forming voltage is 230V, the forming time is 8min, and the secondary formed aluminum foil is obtained; The composite chemical forming liquid b is a mixed solution containing 1wt% boric acid, 0.8wt% citric acid, 0.4wt% ammonium adipate, 0.05wt% ammonium formate, and 0.05wt% ammonium hypophosphite; S3: placing the secondary chemically formed aluminum foil in the composite chemically formed liquid c for third-stage chemically formed, with a chemically formed voltage of 345 V and a chemically formed time of 8 min to obtain a tertiary chemically formed aluminum foil; The composite chemical solution c is a mixed solution containing 1wt% boric acid, 0.4wt% citric acid, 0.2wt% ammonium adipate, and 0.01wt% maleic acid; S4: placing the three-stage chemically formed aluminum foil in the composite chemical forming liquid d for the fourth stage chemical forming, the chemical forming voltage is 455V, the chemical forming time is 8min, and the four-stage chemically formed aluminum foil is obtained; The composite chemical solution d is a mixed solution containing 1wt% boric acid, 0.2wt% citric acid, and 0.1wt% ammonium adipate; S5: placing the four-stage chemically formed aluminum foil in the composite chemical forming liquid e for the fifth stage chemical forming, the chemical forming voltage is 570V, the chemical forming time is 8min, and the five-stage chemically formed aluminum foil is obtained; The composite chemical solution e is a mixed solution containing 8wt% boric acid, 0.01wt% azelaic acid, and 0.04wt% ammonium pentaborate; S6: placing the five-level chemically formed aluminum foil in the composite chemical forming liquid f for the sixth level chemical forming, the chemical forming voltage is 685V, the chemical forming time is 10min, and the six-level chemically formed aluminum foil is obtained; The composite chemical solution f is a mixed solution containing 8wt% boric acid, 0.01wt% azelaic acid, and 0.04wt% ammonium pentaborate; S7: placing the six-stage chemically formed aluminum foil in the composite chemical forming liquid g for the seventh stage chemical forming, the chemical forming voltage is 760V, the chemical forming time is 30min, and the seven-stage chemically formed aluminum foil is obtained; The composite chemical solution g is a mixed solution containing 6wt% boric acid, 0.01wt% azelaic acid, and 0.015wt% ammonium pentaborate; S8: performing the first heat treatment on the seven-level chemically formed aluminum foil, the treatment temperature is 550° C., and the treatment time is 1 min; S9: The aluminum foil after the heat treatment is pressurized to 760V in the composite chemical solution g for the first repair chemical treatment, and the repair chemical treatment time is 10 minutes; then the aluminum foil after the first repair chemical treatment is placed in a 5wt% phosphoric acid solution and treated at 70°C for 15 minutes; S10: The aluminum foil treated with phosphoric acid in step S9 is pressurized to 760V in the composite chemical solution g for a second repair chemical treatment, and the repair chemical treatment time is 10 minutes; S11: subjecting the aluminum foil after the second repair to a second heat treatment, the treatment temperature is 550° C., and the treatment time is 1 min; S12: The aluminum foil after the second heat treatment is pressurized to 760V in the composite chemical liquid g for three repair chemical reactions, and the repair chemical reaction time is 10 minutes; S13: placing the aluminum foil after the third repair in a 0.1wt% phosphoric acid solution and treating it at room temperature for 5 minutes; S14: drying the aluminum foil treated with phosphoric acid in step S13 at 300° C. for 2 min to obtain an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter. Example

[0021] S1: Take a corrosion foil with a corrosion hole diameter of ≥1.4μm, boil it in pure water for 14min; place the boiled corrosion foil in a composite chemical solution a for first-stage chemical formation, with a chemical voltage of 125V and a chemical formation time of 10min to obtain a first-stage chemically formed aluminum foil; The composite chemical liquid a is a mixed solution containing 2wt% of boric acid, 0.7wt% of citric acid, 0.35wt% of ammonium adipate, 0.03wt% of ammonium phthalate, and 0.03wt% of ammonium hypophosphite; S2: placing the primary formed aluminum foil in the composite forming solution b for second-stage forming, the forming voltage is 250, the forming time is 10 min, and the secondary formed aluminum foil is obtained; The composite chemical forming liquid b is a mixed solution containing 2wt% boric acid, 0.6wt% citric acid, 0.3wt% ammonium adipate, 0.03wt% ammonium phthalate, and 0.03wt% ammonium hypophosphite; S3: placing the secondary chemically formed aluminum foil in the composite chemically formed liquid c for the third stage chemically formed, the chemically formed voltage is 370V, the chemically formed time is 10min, and the tertiary chemically formed aluminum foil is obtained; The composite chemical liquid c is a mixed solution containing 2wt% boric acid, 0.3wt% citric acid, 0.15wt% ammonium adipate, and 0.007wt% maleic acid or fumaric acid; S4: placing the three-stage chemically formed aluminum foil in the composite chemical forming liquid d for the fourth stage chemical forming, the chemical forming voltage is 490V, the chemical forming time is 10min, and the four-stage chemically formed aluminum foil is obtained; The composite chemical solution d is a mixed solution containing 2wt% boric acid, 0.15wt% citric acid, and 0.075wt% ammonium adipate; S5: placing the four-stage chemically formed aluminum foil in the composite chemical forming liquid e for the fifth stage chemical forming, the chemical forming voltage is 610V, the chemical forming time is 10min, and the five-stage chemically formed aluminum foil is obtained; The composite chemical solution e is a mixed solution containing 6wt% boric acid, 0.006wt% azelaic acid, and 0.03wt% ammonium pentaborate; S6: placing the five-level chemically formed aluminum foil in the composite chemical forming liquid f for the sixth level chemical forming, the chemical forming voltage is 730V, the chemical forming time is 12min, and the six-level chemically formed aluminum foil is obtained; The composite chemical solution f is a mixed solution containing 6wt% boric acid, 0.006wt% azelaic acid, and 0.02wt% ammonium pentaborate; S7: placing the six-stage chemically formed aluminum foil in the composite chemical forming liquid g for the seventh stage chemical forming, the chemical forming voltage is 810V, the chemical forming time is 35min, and the seven-stage chemically formed aluminum foil is obtained; The composite chemical solution g is a mixed solution containing 5wt% boric acid, 0.005wt% azelaic acid, and 0.01wt% ammonium pentaborate; S8: performing the first heat treatment on the seven-stage chemically formed aluminum foil, the treatment temperature is 550° C., and the treatment time is 2 min; S9: The aluminum foil after the heat treatment is pressurized to 810V in the composite chemical solution g for the first repair chemical treatment, and the repair chemical treatment time is 12 minutes; then the corroded foil after the first repair chemical treatment is placed in a 6wt% phosphoric acid solution and treated at 60°C for 12 minutes; S10: The aluminum foil treated with phosphoric acid in step S9 is pressurized to 810V in the composite chemical solution g for a second repair chemical treatment, and the repair chemical treatment time is 12 minutes; S11: subjecting the aluminum foil after the second repair to a second heat treatment, the treatment temperature is 500° C., and the treatment time is 2 min; S12: The aluminum foil after the second heat treatment is pressurized to 810V in the composite chemical liquid g for three repair chemical reactions, and the repair chemical reaction time is 12 minutes; S13: placing the aluminum foil after the third repair in a 0.08wt% phosphoric acid solution and treating it at room temperature for 3 minutes; S14: drying the aluminum foil treated with phosphoric acid in step S13 at 250° C. for 3 min to obtain an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter. Example

[0022] S1: Take a corrosion foil with a corrosion hole diameter of ≥1.4 μm, and boil it in pure water for 16 minutes; place the boiled corrosion foil in a composite chemical solution a for the first stage chemical formation, the chemical formation voltage is 130V, the chemical formation time is 12 minutes, and a first-stage chemically formed aluminum foil is obtained; The composite chemical liquid a is a mixed solution containing 4wt% of boric acid, 0.4wt% of citric acid, 0.2wt% of ammonium adipate, 0.01wt% of ammonium benzoate, and 0.01wt% of ammonium hypophosphite; S2: placing the primary formed aluminum foil in the composite forming solution b for second-stage forming, the forming voltage is 260V, the forming time is 12min, and the secondary formed aluminum foil is obtained; The composite chemical forming liquid b is a mixed solution containing 4wt% boric acid, 0.4wt% citric acid, 0.2wt% ammonium adipate, 0.01wt% ammonium benzoate, and 0.01wt% ammonium hypophosphite; S3: placing the secondary chemically formed aluminum foil in the composite chemically formed liquid c for third-stage chemically formed, with a chemically formed voltage of 390 V and a chemically formed time of 12 min to obtain a tertiary chemically formed aluminum foil; The composite chemical liquid c is a mixed solution containing 4wt% boric acid, 0.2wt% citric acid, 0.1wt% ammonium adipate, and 0.005wt% maleic acid or fumaric acid; S4: placing the three-stage chemically formed aluminum foil in the composite chemical forming liquid d for the fourth stage chemical forming, the chemical forming voltage is 520V, the chemical forming time is 12min, and the four-stage chemically formed aluminum foil is obtained; The composite chemical solution d is a mixed solution containing 4wt% boric acid, 0.1wt% citric acid, and 0.0wt% ammonium adipate; S5: placing the four-stage chemically formed aluminum foil in the composite chemical forming liquid e for the fifth stage chemical forming, the chemical forming voltage is 640V, the chemical forming time is 12min, and the five-stage chemically formed aluminum foil is obtained; The composite chemical solution e is a mixed solution containing 4wt% boric acid, 0.005wt% azelaic acid, and 0.005wt% ammonium pentaborate; S6: placing the five-level chemically formed aluminum foil in the composite chemical forming liquid f for the sixth level chemical forming, the chemical forming voltage is 765, the chemical forming time is 16min, and the six-level chemically formed aluminum foil is obtained; The composite chemical solution f is a mixed solution containing 4wt% boric acid, 0.01wt% azelaic acid, and 0.005wt% ammonium pentaborate; S7: placing the six-stage chemically formed aluminum foil in the composite chemical forming liquid g for the seventh stage chemical forming, the chemical forming voltage is 850V, the chemical forming time is 40min, and the seven-stage chemically formed aluminum foil is obtained; The composite chemical solution g is a mixed solution containing 4wt% boric acid, 0.01wt% azelaic acid, and 0.005wt% ammonium pentaborate; S8: performing the first heat treatment on the seven-level chemically formed aluminum foil, the treatment temperature is 450° C., and the treatment time is 3 min; S9: The aluminum foil after the heat treatment is pressurized to 850V in the composite chemical solution g for the first repair chemical treatment, and the repair chemical treatment time is 15 minutes; then the corroded foil after the first repair chemical treatment is placed in a 5wt% phosphoric acid solution and treated at 70°C for 10 minutes; S10: The aluminum foil treated with phosphoric acid in step S9 is pressurized to 850V in the composite chemical solution g for a second repair chemical treatment, and the repair chemical treatment time is 15 minutes; S11: subjecting the aluminum foil after the second repair to a second heat treatment, the treatment temperature is 450° C., and the treatment time is 3 min; S12: The aluminum foil after the second heat treatment is subjected to three repairing and forming operations by pressurizing to 850V in the composite forming liquid g, and the repairing and forming time is 15 minutes; S13: placing the aluminum foil after the third repair in a 0.05wt% phosphoric acid solution and treating it at room temperature for 5 minutes; S14: drying the aluminum foil treated with phosphoric acid in step S13 at 200° C. for 4 minutes to obtain an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter.

[0023] The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter, characterized in that: The following steps are involved: S1: Take a large-aperture etched foil and boil it in pure water for 12 to 16 minutes; place the boiled etched foil in a composite chemical solution a for first-stage chemical formation, with a chemical voltage of 15% of the applied voltage and a chemical time of 8 to 12 minutes to obtain a first-stage chemically formed aluminum foil; The composite chemical liquid a is a mixed solution containing 1-4wt% boric acid, 0.4-1.0wt% citric acid, 0.2-0.5wt% ammonium adipate, 0.01-0.05wt% ammonium formate or ammonium phthalate or ammonium benzoate, and 0.01-0.05wt% ammonium hypophosphite; S2: placing the primary chemically formed aluminum foil in the composite chemically formed liquid b for the second stage chemically formed, the chemically formed voltage is 30% of the applied voltage, the chemically formed time is 8 to 12 minutes, and the secondary chemically formed aluminum foil is obtained; The composite chemical forming liquid b is a mixed solution containing 1-4wt% boric acid, 0.4-0.8wt% citric acid, 0.2-0.4wt% ammonium adipate, 0.01-0.05wt% ammonium formate or ammonium phthalate or ammonium benzoate, and 0.01-0.05wt% ammonium hypophosphite; S3: placing the secondary chemically formed aluminum foil in the composite chemically formed liquid c for the third chemically formed, the chemically formed voltage is 45% of the applied voltage, the chemically formed time is 8 to 12 minutes, and the tertiary chemically formed aluminum foil is obtained; The composite chemical liquid c is a mixed solution containing 1-4wt% boric acid, 0.2-0.4wt% citric acid, 0.1-0.2wt% ammonium adipate, and 0.005-0.01wt% maleic acid or fumaric acid; S4: placing the three-stage chemically formed aluminum foil in the composite chemical liquid d for the fourth stage chemically forming, the chemically forming voltage is 60% of the applied voltage, the chemically forming time is 8 to 12 minutes, and the four-stage chemically formed aluminum foil is obtained; The composite chemical liquid d is a mixed solution containing 1-4wt% boric acid, 0.1-0.2wt% citric acid, and 0.05-0.1wt% ammonium adipate; S5: placing the four-stage chemically formed aluminum foil in the composite chemical liquid e for the fifth stage chemically formed, the chemically formed voltage is 75% of the applied voltage, the chemically formed time is 8 to 12 minutes, and the five-stage chemically formed aluminum foil is obtained; The composite chemical solution e is a mixed solution containing 4-8wt% boric acid, 0.005-0.01wt% azelaic acid, and 0.005-0.1wt% ammonium pentaborate; S6: placing the five-level chemically formed aluminum foil in the composite chemically formed liquid f for the sixth level chemically formed, the chemically formed voltage is 90% of the voltage to be applied, the chemically formed time is 10 to 16 minutes, and the six-level chemically formed aluminum foil is obtained; The composite chemical liquid f is a mixed solution containing 4-8wt% boric acid, 0.002-0.01wt% azelaic acid, and 0.005-0.04wt% ammonium pentaborate; S7: placing the six-stage chemically formed aluminum foil in the composite chemical forming liquid g for the seventh stage chemical forming, the chemical forming voltage is 100% of the voltage to be applied, the chemical forming time is 30 to 40 minutes, and the seven-stage chemically formed aluminum foil is obtained; The composite chemical liquid g is a mixed solution containing 4-6wt% boric acid, 0.001-0.01wt% azelaic acid, and 0.005-0.015wt% ammonium pentaborate; S8: performing a first heat treatment on the seven-level chemically formed aluminum foil, the treatment temperature is 450-550° C., and the treatment time is 1-3 min; S9: performing a first repair chemical treatment on the heat-treated aluminum foil, the repair chemical treatment time being 10 to 15 minutes; then placing the aluminum foil after the first repair chemical treatment in a 5 to 8 wt % phosphoric acid solution, and treating at 55 to 70° C. for 10 to 15 minutes; S10: performing a second repair and chemical treatment on the aluminum foil after the phosphoric acid treatment in step S9, and the repair and chemical treatment time is 10 to 15 minutes; S11: subjecting the aluminum foil after the second repair to a second heat treatment, the treatment temperature is 450-550° C., and the treatment time is 1-3 min; S12: The aluminum foil after the second heat treatment is repaired and formed three times, and the repairing and forming time is 10 to 15 minutes; S13: placing the aluminum foil after the third repair in a 0.05-0.1 wt % phosphoric acid solution and treating it at room temperature for 1-5 min; S14: drying the aluminum foil treated with phosphoric acid in step S13 at 200-300° C. for 2-4 minutes to obtain an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter.

2. The method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter according to claim 1, characterized in that: The diameter of the corrosion holes of the large-aperture corrosion foil is ≥1.4 μm.

3. The method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter according to claim 1, characterized in that: The voltage to be applied is 760V to 850V.

4. The method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter according to claim 3, characterized in that: The repairing formation is carried out in the composite formation liquid g.

5. The method for forming an electrode foil for an aluminum electrolytic capacitor of a photovoltaic inverter according to claim 4, characterized in that: The repair formation voltage is 100% of the applied voltage.